Perencanaan Keuangan Pribadi: Bagaimana Mimpi Menjadi Tujuan - Putra, Dimas Pratama; Firmansyah Arifin; Sulbahri, Rifani Akbar (Jurnal Pemberdayaan Masyarakat, 2024)
Many people wish to have healthy finances in which they are not under financial stress. However, due to a lack of understanding (financial literacy), many people can just dream and cannot plan healthy personal finances. Only 40% of residents in Palembang City's Sako District complete personal financial planning, as determined by a survey conducted by 100 persons. This community program seeks to educate participants on the necessity of personal financial planning and how to create personal financial statements toÂ attain financial goals. The residential area in Sako District, Palembang City, has been designated as the target for community service (PKM) implementation. This research provides learning using mentoring and discussion methods. The results revealed an average of 20 Participants Financially stressless, 1 Participant Financially Stressed, 1 Participant Financially Shocked, and 1 Participant Financially stressfree. Thus, the average participant's basic financial condition is usually less stressful and worrying, but investment and protection are still minimal so they are worried about causing problems in the future.